2018
DOI: 10.3934/nhm.2018011
|View full text |Cite
|
Sign up to set email alerts
|

Stability and implementation of a cycle-based max pressure controller for signalized traffic networks

Abstract: Intelligent use of network capacity via responsive signal control will become increasingly essential as congestion increases on urban roadways. Existing adaptive control systems require lengthy location-specific tuning procedures or expensive central communications infrastructure. Previous theoretical work proposed the application of a max pressure controller to maximize network throughput in a distributed manner with minimal calibration. Yet this algorithm as originally formulated has unpractical hardware and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Pumir et al ( 26 ) provide a cyclic extension to MP control with performance gains observed in simulation results. Anderson et al ( 27 ) alter the MP formulation to a cyclic MP controller which performs better than actuated signal controllers. These cyclic MP controllers however require a predefined fixed cycle length, which requires manual fine-tuning based on predicted demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pumir et al ( 26 ) provide a cyclic extension to MP control with performance gains observed in simulation results. Anderson et al ( 27 ) alter the MP formulation to a cyclic MP controller which performs better than actuated signal controllers. These cyclic MP controllers however require a predefined fixed cycle length, which requires manual fine-tuning based on predicted demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Decentralized feedback policies for control such as max-pressure [28] address these issues by adjusting phase splits based on differences in upstream and downstream queue lengths. Maxpressure is stable and provides guaranteed bounds for queues and delay under store and forward queuing system [29], but is challenging to implement in real settings due to its hardware and safety constraints [30], [31].…”
Section: A Model-based Coordination Controlmentioning
confidence: 99%
“…Several other cyclic algorithms have since been proposed including two by Pumir et al ( 11 ) and Anderson et al ( 12 ) which both had a fixed cycle length. An algorithm by Levin et al ( 13 ) also had a cyclic structure but allowed the cycle length to be lengthened or shortened in response to real-time demand.…”
Section: Introductionmentioning
confidence: 99%